A Door Opens for Fibrodysplasia Ossificans Progressiva. Issue 2 (February 2016) - Katagiri, Takenobu
Abstract : Fibrodysplasia ossificans progressiva (FOP), characterized by extra bone formation in soft tissues, is caused by a gain-of-function mutation in ACVR1, a transmembrane receptor. Recently, a potential treatment was developed by identifying a novel molecular mechanism underlying bone formation in FOP. These findings have opened the door to beating FOP.